Peningkatan Perceived Customer Value Perumahan Western Village di Surabaya melalui Penerapan Kualitas Produk dan Perceived Service Quality - I Made Bagus; Prita Ayu Kusumawardhany (Universitas Negeri Surabaya, 2017)
This study aims to test and analyze customer value enhancement of the Western Village Housing in Surabaya perceived through the application of product quality and the perceived quality of service. This study uses the free variable that is perceived of product quality and the perceived quality of service, as well as variable customer value. This study included in this type of research surveys that are used for the purpose of explanation or confirmatory, or also called research for testing hypotheses to explain the influences between variables or causal relationship between variables through the hypothesis testing. A sample of these studies amounted to 108 respondents consisting of customer Western Village in Surabaya. Sampling techniques in the study was done by accidental sampling method. The data obtained through the distribution and collection of returned questionnaires and then analyzed using SPSS. A model of the relationship between the variables examinedproduce perceived of product quality and the perceived quality of service that has important relations towards customer value Housing Western Village in Surabaya. The results of this study alsohas important meanings especially for Housing Management Western Village in Surabaya in applying perceived of product quality and the perceived quality of service so that our customer optimal value.